Kohesi dalam Novel Surat Kecil untuk Tuhan - SRI PUJI ASTUTI (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This study uses the Surat Kecil untuk Tuhan novel (NSK) as a data source. The language used in this novel is very interesting. Therefore, cohesion is used in this novel as a marker. This study aims to decipher lexical cohesion markers and grammatical cohesion markers used in the Surat Kecil untuk Tuhan. In collecting data, the researchers first listened to the use of the language used in the novel then continued with the note taking technique. The results of the analysis found that to form a coherent discourse the author of the Surat Kecil untuk Tuhan uses lexical cohesion markers and grammatical cohesion markers.